Indonesian government policies: catalyzing economic growth in food Iindustry expansion - Nurhayati Nurhayati (Jurnal Mantik, 2024)
This study examines the significant impact of Indonesian government policies on the economic development of the country, particularly in relation to the food industry. The study utilizes Comparative Analysis to investigate the historical development of policy measures, specifically the shift from import substitution to export-led growth. It evaluates the effects of these measures on the productivity, sustainability, and global competitiveness of the food industry. This analysis carefully examines a large amount of data from the Indonesian Ministry of Agriculture, BPS Indonesia, and other reliable sources to reveal the complex connection between policy interventions and economic performance measures such as GDP growth, employment, and investment in the food sector. The findings highlight the crucial impact of deliberate government investments in stimulating the food industry's involvement in Indonesia's economic stability and sustained progress. Furthermore, the study emphasizes the significance of taking into account contextual elements when evaluating policies and recognizing the external influences that impact economic results. This research provides valuable recommendations for refining policies and guiding future research to improve the effectiveness of government initiatives in promoting economic growth and innovation in Indonesia's food industry. It achieves this through a thorough understanding of the impacts of policies and by comparing different insights